HUBUNGAN KARAKTERISTIK NARAPIDANA, PREFERENSI PENAMPILAN, RASA, DAN MENU MAKANAN DENGAN SISA MAKANAN (Studi di Lembaga Pemasyarakatan Klas IIA Wanita Semarang Tahun 2016) - Sarah Khalda Azzahra; Suyatno Suyatno; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Food service for prisoners is one of the efforts to improve the health and nutritional status. The success of nutritional services if the food is not more than 25%. If plate waste are still left in a period of time, it will cause a deficiency of nutrients. The purpose of this research is to determine the correlation between prisoners characteristics, preferences of food appearance, food taste, and food menu with plate waste. This research is a quantitative research with cross sectional approach. Respondents of this research were 72 female prisoners. The sampling technique used purposive sampling. The variables of age, education, food appearance, food taste, and food menu with plate waste were analyzed using Spearman Rank test and ethnic variable with plate waste was analyzed using Chi Square. The results showed that respondents aged less than 35 years was 54.2%, respondents from ethnic Javanese was 51.4%, and respondents had a higher education level was 65.3%. Respondents represented that the preference of food appearance was interesting (55.6%) with an average of 2,82, the preference of food taste was delicious (72.2%) with an average of 2,90, the preference of food menu was varied (56.9%) with an average of 2,69, and the plate waste with the high category (>25%) was 54.2% with an average of 27%. The highest plate waste based on the type of food was staple food (40%) and snacks (31%). The highest plate waste based on mealtime was dinner time (30%). Analysis result showed that there were no correlation of age (p=0.631), ethnicity (p=0.150), education (p=0.120), food appearance (p=0.075), food taste (p=0.051), and food menu (p=0.206) with plate waste. Improve the quality of food especially in food portions, food temperature, and food seasoning and need innovation on the food menu so that the prisoners don’t feel bored.